Les encyclopédismes en France à l'ère des révolutions (1789-1850) - Bourdeau, Vincent; Chappey, Jean-Luc; Vincent, Julien (Les Cahiers de la MSHE Ledoux, 2020)
After the French Revolution, the idea of an encyclopedia took on a considerable scope. Until the Spring of the Peoples in 1848, it was inseparable from the idea of a universal republic, and was at the heart of a multiplicity of challenges for the institutional, intellectual and political reconstruction of post-revolutionary society. It is to the singularity of this moment (1789-1848) in the long history of encyclopedism that the various contributions in this volume are dedicated. Far from being limited to a moment in the history of science, encyclopedism reveals to us the way in which modern societies represent themselves and establish themselves politically.